Escherichia coli, Species C Human Adenovirus, and Enterovirus in Water Samples Consumed in Rural Areas of Goiás, Brazil - Lima, Fernando Santos; Scalize, Paulo Sérgio; Gabriel, Ellen Flávia Moreira; Gomes, Raylane Pereira; Gama, Aline Rodrigues; Demoliner, Meriane; Spilki, Fernando Rosado; Vieira, José Daniel Gonçalves; Carneiro, Lilian Carla (Food and environmental virology, 2022)
Rural environments lack basic sanitation services. Facilities for obtaining water and disposing sewage are often under the initiative of each resident, who may not be able to build and maintain them properly. Thus, water for human consumption is subject to fecal contamination and, consequently, the presence of waterborne pathogens, such as enteric viruses. This study evaluated fecal contamination of water samples from individual sources used for domestic water supply on small farms in the state of Goiás, Brazil. Samples were collected from 78 houses whose water sources were tubular wells, dug wells, springs, and surface waters. Escherichia coli (EC) bacteria, analyzed by the defined chromogenic substrate method, was used as a traditional indicator of fecal contamination. The enteric viruses Human mastadenovirus (HAdV) and Enterovirus (EV), analyzed by qPCR, were tested as complementary indicators of fecal contamination. At least one of these markers was found in 89.7% of the samples. Detection rates were 79.5% for EC, 52.6% for HAdV, and 5.1% for EV. The average concentration for EC was 8.82 × 10 1 most probable number (MPN) per 100 mL, while for HAdV and EV the concentrations were 7.51 × 10 5 and 1.89 × 10 6 genomic copies (GC) per liter, respectively. EC was the most frequent marker in ground and surface water samples. HAdV was detected significantly more frequently in groundwater than in surface water and was more efficient in indicating contamination in tubular wells. There was no association of frequencies or correlation of concentrations between EC and HAdV. HAdV indicated human fecal contamination and performed well as a complementary indicator. The results reveal that a large part of the analyzed population is vulnerable to waterborne diseases caused by enteric pathogens.